Practitioner research: Teachers' investigations in classroom teaching - Khine, Myint Swe; Saleh, I. (Nova Science Publishers, Inc., 2011)
Practitioner research is not a new concept in education and many teachers had attempted to enact and study their own practices with the view of improving teaching effectiveness. Over the past decade there has been increased interests in teachers' investigation of own practice in their classrooms. However, the findings of many of these studies are often not treated seriously by education scholars and policymakers, and not widely disseminated to others. This book identifies pertinent issues related to practitioner research and describes recent attempts in theorizing teacher research, outlining research agenda, promoting the culture of teacher-led research, building capacity, developing models and examining current thinking about practitioner research. © 2011 by Nova Science Publishers, Inc. All rights reserved.